2000
DOI: 10.1177/027112140002000202
|View full text |Cite
|
Sign up to set email alerts
|

The Federal Role in Early Intervention

Abstract: Since 1968, the federal government has played an essential role in establishing and implementing early intervention and preschool services for young children with disabilities and their families. This has been accomplished through a series of laws, regulations, supports, and incentives that collectively have shaped the nature and extent of current practice. I predict that as we enter the new millennium, we will not see new major legislation comparable in impact to IDEA and ADA. There will be a continued shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Though the findings of this project provided strong theoretical and anecdotal empirical support for the support the provision of comprehensive services and supports at an early age in order to prevent more serious, long-term outcomes, rigorous empirical replications of meaningful outcomes remain in need (Bailey, 2000(Bailey, , 2001Bailey, McWilliam, Darkes, Hebbeler, Simeonsson, Spiker, & Wagner, 1998;Carta, 2002;Guralnick, 2000;Turnbull & Turnbull, 2000). Given the fact that over 200,000 children and families receive Part C early intervention services and supports in the United States (Hebbeler, Spiker, Mallik, Scarborough, & Simeonsson, 2003;U.S.…”
Section: Building a Rationale For Early Intervention Servicesmentioning
confidence: 98%
See 1 more Smart Citation
“…Though the findings of this project provided strong theoretical and anecdotal empirical support for the support the provision of comprehensive services and supports at an early age in order to prevent more serious, long-term outcomes, rigorous empirical replications of meaningful outcomes remain in need (Bailey, 2000(Bailey, , 2001Bailey, McWilliam, Darkes, Hebbeler, Simeonsson, Spiker, & Wagner, 1998;Carta, 2002;Guralnick, 2000;Turnbull & Turnbull, 2000). Given the fact that over 200,000 children and families receive Part C early intervention services and supports in the United States (Hebbeler, Spiker, Mallik, Scarborough, & Simeonsson, 2003;U.S.…”
Section: Building a Rationale For Early Intervention Servicesmentioning
confidence: 98%
“…Given the fact that children are eligible for the early intervention program until 36 months of age, the duration of enrollment and access to available services is drastically reduced. Though services are available for children between three to five years of age, the model of service delivery and the frequency, intensity, and duration of its services are different and often less individualized (Bailey, 2000;Bredekamp, 1991;Carta, Schwartz, Atwater, & McConnell, 1991;Florida Department of Education, 1998;Guralnick, 2000).…”
Section: Commentedmentioning
confidence: 99%
“…As predicted by Bailey (2000), ongoing research focuses less on th e child's IQ or developmental quotient as desirable child-based outcomes, bu t rather on which services provide the needed support to families raising thes e children (e .g., Guralnick, 1997a;Malone et al ., 2000;Wolery & Bailey, 2002) .…”
Section: Focus On Familiesmentioning
confidence: 99%
“…No published research was found that was conducted on the earl y intervention or early childhood special education needs or experiences of mobil e move from one state to another and realize the differences, there is very little time before their child (sic) moves into the Part B service system, and thus th e considerable variation in infant services is not so evident" (Bailey, 2000) . This certainly is not the experience of military families, who move throughout the lif e spans of their children and are acutely aware of service differences in their ne w locations .…”
Section: Research On Mobility and Military Familiesmentioning
confidence: 99%
“…Not surprising, these inherent differences in how states organize and deliver early intervention services are reflected in their Part C data systems. The inconsistencies in states' Part C data systems represent a tremendous obstacle in the creation of a national Part C data base, even though a number of researchers have acknowledged the value of such populationbased data for informing decisions related to improving the quality, intensity, and outcomes of early intervention services (Bailey, 2000;Spiker et al, 2000).…”
mentioning
confidence: 99%